CESifo World Economic Survey November 2005 - Gernot Nerb; Anna Stangl (CESifo World Economic Survey, 2005)
World Economic Climate: World Economic Climate brightens up Economic Expectations: Assessments of current economic situation improved, economic expectations somewhat less positive Inflation: Inflation expectations for 2005 revised upwards Interest Rates: Trend of rising rates not yet expected to slow down Currencies: US dollar seen as fairly assessed and the euro to a less degree as overvalued
Keywords: 330